Manager characteristics and top management team in antioquia's manufacturing SMES [Características gerenciales y del equipo de alta gerencia en las PYMES antioqueñas del macrosector de manufacturas] (2017)
This paper presents a description of the main features of managers and the Top Management Team (TMT) of small and medium-sized enterprises (SME) belonging to the manufacturing sector that develop activities of internationalization in Colombia. Through the development of telephone and virtual surveys, management characteristics of SME in the city of Medellin (Colombia) during 2015 were consulted. It was identified that the organizational composition of SME lies primarily in the figure of the manager, and that even under the existence of the figure of top management team in some companies, decision-making in activities of internationalization is concentrated in the manager. © 2017.